Building a Competent Early Childhood Education and Care Workforce in the Asia-Pacific Region. Issue 1 (1st January 2022) - Luo, Wenwei; Berson, Ilene R.; Berson, Michael J.
ABSTRACT: In the midst of the COVID-19 worldwide pandemic, the virtual home visit became a key strategy among China's multiple approaches to ensure children's continuity of learning, sustain teacher-parent-child relationships, and promote home–preschool collaboration. In this study, using a small stories research narrative paradigm to analyze documented family engagement captured in social media data, we explore how early childhood educators relied on frequent, personal connections with children and families through virtual home visits to mitigate the negative effects of preschool closures in China. Results suggest that the exchange of information and socio-emotional supports during virtual home visits supported and enhanced home–preschool relationships. The virtual home visits evolved into a space for connection and collaboration between the educators and families. We use an ecological-exchange framework to discuss the implications of virtual home visit experiences across time and reflect on pedagogy and practice to enhance development of teachers in online interactions with children and families.